Love me tonight - 2 Bass Hit; Eddy Ouwens Productions (Netherlands : Eddy Ouwens Productions, 1996)
Contains four techno pop tracks.
CD 1 : Love Me Tonight (Hardcore Edit-Pulpshock & Mac Attack) / (3:14) -- Love Me Tonight (radio edit) / (3:49) -- Jazz House (extended version) / (5:16) -- Guarana Moods (Mo'betterfunkforyourearandbuttmix) / (5:01).
Koleksi Khas Wiramanja.
2 Bass Hit are Peter Kardolus (Sax) and Patrick van Herrikhuyzen (Keys/Piano).
Title from disc label.
Keywords: Songs, English